2022
DOI: 10.1186/s12886-022-02461-4
|View full text |Cite
|
Sign up to set email alerts
|

Axial length shortening after orthokeratology and its relationship with myopic control

Abstract: Purpose To determine the pattern of axial variation in subjects with initial shortened axial length during the entire period of orthokeratology and to discuss the possibility of shortened AL after one month of orthokeratology becoming a predictor of myopia control. Method This study retrospectively included 106 children with myopia aged 8 to 14 wearing OK lenses. Fifty-four eyes with shortened axial length (AL) at the first-month visit were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 43 publications
(58 reference statements)
2
20
0
Order By: Relevance
“…AL shortening is a phenomenon that is rarely reported following myopia control treatments. Short-term decreases in AL have been reported following orthokeratology treatment, 24 , 25 and persistent AL shortening was reported in a 4-year-old child given violet light-transmitting eyeglasses, which led to −0.20 AL over 2 years. 26 In the ATOM1 study, AL shortened −0.14 mm in subjects using 1% atropine eye drops, but the proportion and range were not reported.…”
Section: Discussionmentioning
confidence: 97%
“…AL shortening is a phenomenon that is rarely reported following myopia control treatments. Short-term decreases in AL have been reported following orthokeratology treatment, 24 , 25 and persistent AL shortening was reported in a 4-year-old child given violet light-transmitting eyeglasses, which led to −0.20 AL over 2 years. 26 In the ATOM1 study, AL shortened −0.14 mm in subjects using 1% atropine eye drops, but the proportion and range were not reported.…”
Section: Discussionmentioning
confidence: 97%
“…Including additional lens types could improve the accuracy and efficiency of the machine learning model for a broader OK lens market. In addition, Wang et al 35 reported that short periods of axial length change could be used as a predictor of long‐term myopia development. Therefore, the machine learning model included the initial changes that could increase the accuracy of the axial length prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…The first AL was defined as the first AL after ortho-k lens wear for at least 6 months to avoid the fluctuation of AL at the early stage of ortho-k lens wear around 1 to 3 months. 2,23…”
Section: Methodsmentioning
confidence: 99%
“…AL after ortho-k lens wear for at least 6 months to avoid the fluctuation of AL at the early stage of ortho-k lens wear around 1 to 3 months. 2,23 Ortho-K Lenses All children were treated with ortho-k lenses by the same brand (DreimLens). Astigmatic lenses were also prescribed for improved centration as required.…”
Section: Measurement Of Relative Distances and Grayscale Of Lpap To D...mentioning
confidence: 99%